Uso do hidrolato de Myrcia Sylvatica (G.Mey.) DC. (Myrtaceae) como sedativo em condições simuladas de transporte de juvenis de Tambaqui (Colossomoma macropomum). - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
The use of natual products in aquaculture has been intensifying, appearing as an alternative for improvement in production as food supplements, insecticides, anesthetics and sedatives. The objective of this work was to evaluate the use of the Myrcia sylvativa hydrolate (HMS) under simulated conditions of transport of tambaqui (Colossoma macropomum) juveniles at different densities. Tambaqui juveniles (3 to 5 cm) were placed in plastic bags. For a 17 h simulated transport at loading densities of 30, 60 and 90 juveniles/L in three concentrations of HMS (2.5, 5 and 7.5%) and control water (CA). Survival was verified immediately after transport and after 24h (characterized as post-transport). The physical and chemical parameters of the water were evaluated before and after the transport (temperature, pH, alkalinity, hardness, dissolved oxygen, electrical conductivity and total dissolved solids), as well as the net flow of Na+ , K+ , Clions and excretion of ammonia. In addition, the density of gill mucous cells was observed after transport. There was no significant difference in survival between treatments and densities. Temperature, hardness, total and non - ionized ammonia showed no significant difference between treatments and density. However, the pH presented a difference even at the initial values, reducing as a function of the increase in HMS concentration. The dissolved oxygen was significantly lower when the initial and final values were compared. Alkalinity and total dissolved solids increased significantly as a function of density. The conductivity and ionic flow (Na+ , K+ , Cl- . were lower in the treatment with 5% HMS mainly at higher density. The number of mucosal cells neutral and acidic gills was lower in 5% HMS at the higher charge density. The use of HMS at 5% concentration may be recommended for the transport of long-lived tambaqui juveniles 17h. Although it did not differ significantly from the control group in the percentage of survival, however, it presented low fluctuations in pH values at all densities and at the density of 90 fish / L it reduced the efflux of Na+ and K + and Clions, and did not stimulated the production of neutral and acidic gill mucosal cells, which proved to be a potential stress reducer and effective at higher densities. This work is the first study with the use of Myrcia sylvativa hydrolate with application in aquaculture management.
Keywords: Sobrevivência; Qualidade da água; Fluxo iônico; Células mucosas.; CNPQ: GEOCIÊNCIAS; RECURSOS NATURAIS; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSTECÇÃO NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO